Communicating authoritarian elite cohesion. Issue 1 (2nd January 2016) - Schedler, Andreas; Hoffmann, Bert
Abstract : In this paper, we develop a theoretical framework to analyse the communicative imperatives authoritarian regimes face as a consequence of their self-inflicted opacities. The most important facts about the actors and factors that sustain authoritarian rule are unobservable. To demonstrate their power, authoritarian rulers have to render them visible. They have to dramatize their power and present on the front stage what they want people to know about the backstage of authoritarian politics. We conceptualize the communicative strategies of authoritarian rulers with a focus on the primary existential threats they face: the lateral threats that emanate from within the authoritarian elite. We illustrate dictators' communicative repertoire with empirical material from communist Cuba from 2006 to 2011, during the critical juncture of leadership transition from Fidel Castro to his brother Raúl.